1 x 7 plus 2 x 7 is the same as 3 x 7
To find 6x7 using 3x7, you can simply double the result of 3x7. This is because multiplication is distributive over addition, meaning that multiplying a number by a sum is the same as multiplying the number by each addend and then adding the products. In this case, 6x7 can be thought of as (3+3)x7, which equals 3x7 + 3x7, or 21 + 21, which equals 42.
3(7 + 2) = 3x7 + 3x2 is an example of the distributive law.The distributive law connects multiplication and addition.
3x7 = 21
y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2
21x1 and 3x7
1 x 7 plus 2 x 7 is the same as 3 x 7
I think 7x3 is = to 21
To find 6x7 using 3x7, you can simply double the result of 3x7. This is because multiplication is distributive over addition, meaning that multiplying a number by a sum is the same as multiplying the number by each addend and then adding the products. In this case, 6x7 can be thought of as (3+3)x7, which equals 3x7 + 3x7, or 21 + 21, which equals 42.
3(7 + 2) = 3x7 + 3x2 is an example of the distributive law.The distributive law connects multiplication and addition.
2x7 = 14 x7 = 7 3x7 = 3*7 = 21
6 x 7 is equal to 2 x 3 x 7. If you find the solution to 3 x 7, you can multiply it by 2 to get 6 x 7.
3x7 = 21
y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2
3x7
21
-21